Using an Automated Operant Conditioning Procedure to Test Colour Discrimination in Two Juvenile Piranhas, Pygocentrus nattereri: A Lesson on Failures and Pitfalls and How to Avoid Them - Christian Agrillo; Alessandra Pecunioso (Animals)
Most studies on the cognitive abilities of fish have focused on model organisms adopted in behavioural neuroscience. To date, little attention has been devoted to characiformes fish and we record a lack of cognitive investigation on the piranha. In this study, we conducted a preliminary set of experiments to assess whether red-bellied piranhas (Pygocentrus nattereri) can solve an automated operant conditioning task, specifically, a reversal learning task. In Experiment 1, the fish were required to discriminate between red and green, while in Experiment 2, they had to discriminate between white and yellow. In either case, we found no evidence of learning capacities with our protocol after extensive training exceeding one thousand trials overall. In Experiment 3, we simplified the learning task by using achromatic stimuli (black and white discrimination) and always presenting the reinforced stimulus on the same side of the tank (a combination of response learning and place learning). Subjects did learn how to discriminate between the colours, although no subject was able to reach the criterion in the subsequent reversal learning task, suggesting that piranhas may be limited in their cognitive flexibility. However, our training procedure may have been inefficient in addressing this issue. We outline some potential limitations of the current methodology to help to establish a more effective approach for investigating operant conditioning in this species.